Laparoscopic Versus Open Gastric Wedge Resection for Primary Gastrointestinal Tumors: Clinical Outcomes and Health Care Costs Analysis. Issue 2 (April 2015) - de'Angelis, Nicola; Brunetti, Francesco; Felli, Emanuele; Mehdaoui, Dalila; Memeo, Riccardo; Carra, Maria Clotilde; Zuddas, Valeria; Azoulay, Daniel
Abstract : The study aimed to compare laparoscopic wedge resection (LWR) versus open-wedge resections (OWR) for primary gastrointestinal stromal tumors (GISTs) of the stomach. Twenty-five patients who underwent LWR were matched by tumor size and location with 25 patients who underwent OWR. GISTs close to the pylorus or the esophagogastric junction, incidental, and metastatic GISTs were excluded. Demographic, clinical, and histologic variables did not differ between groups. Estimated blood loss, time to flatus, and duration of hospitalization were significantly lower in the LWR group. Overall, 6 patients developed minor postoperative complications that were medically treated. Mortality was nil. No group difference was observed for the incidence of diseases during the follow-up (average, 46.8 mo). The OWR procedure had significantly higher costs (+34%) than the LWR. Both techniques appear safe and oncologically feasible. However, laparoscopy is associated with faster recovery and shorter hospital stay, which reflect advantages in terms of contracted costs for the health care system.